Od Konkursu Piosenkarzy Amatorów po Festiwal Piosenki Radzieckiej. Rozwój imprezy w latach 1962-1965 = From Contest of Amateur Singers to Festival of Soviet Song. Festival ?s development between 1962-1965 - Marczak, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the beginning of Festival of Soviet Song in Zielona Gora - one of the greatest and the most promoted music event in The Polish People?s Republic. The authoress answers a question where the idea of organization such festival in 1962 derives from.
Keywords: Festiwal Piosenki Radzieckiej; Zielona Góra; kultura - historia; imprezy masowe; propaganda; The Soviet Song Festival; history of culture; mass events